PENGARUH KEPRIBADIAN DAN QUALITY OF WORK LIFE TERHADAP KINERJA DENGAN MEDIASI ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN KOMITMEN ORGANISASIONAL ( Studi Pada Kantor Sekretariat Provinsi Jawa Tengah ) - Kristianti, Mei; Soliha, Euis (Jurnal Ilmiah Telaah Manajemen, 2015)
This study aimed to analyze the influence of personality and Quality Of Work Life on the performance ofthe mediation organizational citizenship behavior and organizational commitment ( studies in Central Java provincial secretariat office ) . In a study using census method with a total population of 105 respondents. Test used is a test instrument with testing using multiple regression analysis. Test models using test R2( coefficient of determination ) and F test the hypothesis testing is using the t test. Based on the results of the study can be summarized as follows; 1 ) personality positive and significant effect on OCB, 2 ) QWL positive and significant effect on OCB, 3 ) personality positive and significant effect on organizational commitment, 4 ) QWL positive and significant effect on organizational commitment, 5 ) personality positive and significant effect on performance, 6 ) QWL positive and significant effect on performance. 7 ) OCB positive and significant impact on performance, 8 ) organizational commitment is positive and significant impact on performance, 9 ) OCB does not mediate the effect of personality on performance. 10 ) . OCB does not mediate the effect QWL on OCB. 11 ) . Organizational commitment mediates the influence of personality on performance. 12 ) . Organizational commitment meemediasi QWL influence on performance.Keywords: orgnisasional commitment, competence, job satisfaction, organizational citizenship behavior and performance